Impedance relations for differential antennas and single-ended counterparts - Zhang, Yue Ping (2022)
The impedance parameters of a two-port network are employed to deduce the differential and common-mode as well as single-ended input impedances of a differential antenna. The relationships between these impedances are considered. It is shown that there exist simple quantitative relations, which may be used to determine one impedance from the other whose solution is already known. In addition, an important attempt is made to extend Booker's relation for differential complementary dipoles and slots to single-ended counterparts.